Composite solid electrolyte membrane and semi-solid lithium ion battery

By covering the oxide solid electrolyte layer on the surface of the halide/sulfide solid electrolyte film, the problem of chemical reaction between the halide/sulfide solid electrolyte and the liquid electrolyte is solved, the application of semi-solid lithium-ion batteries is realized, and the cycle stability of the battery is significantly improved.

CN119742431APending Publication Date: 2025-04-01HUACAI (HEFEI) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510029765.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Chemical reactions are prone to occur between halide/sulfide solid electrolyte and liquid electrolyte, causing electrolyte to deteriorate and cannot be effectively applied to semi-solid lithium-ion batteries.

Method used

The oxide solid electrolyte layer is coated on the surface of the halide/sulfide solid electrolyte film to prevent liquid electrolyte from penetrating into contact with the sulfide/halide solid electrolyte and prevent chemical reactions.

Benefits of technology

The chemical reaction between sulfide/halide solid electrolyte and liquid electrolyte is effectively avoided, the interface stability is improved, the application of composite solid electrolyte membrane in semi-solid lithium-ion batteries is realized, and the circulation stability is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742431A_ABST
    Figure CN119742431A_ABST
Patent Text Reader

Abstract

The present invention discloses a composite solid electrolyte membrane and a semi-solid lithium ion battery, wherein the composite solid electrolyte membrane comprises a halide / sulfide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide / sulfide solid electrolyte film. The composite solid electrolyte membrane and the semi-solid lithium ion battery provided by the present invention effectively avoid the reaction between the sulfide / halide solid electrolyte and the liquid electrolyte by coating the surface of the halide / sulfide solid electrolyte film with an oxide solid electrolyte layer having high chemical stability to organic solvents, thereby enabling the composite solid electrolyte membrane to be effectively applied to a solid-liquid mixed semi-solid lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a composite solid-state electrolyte membrane and a semi-solid-state lithium-ion battery. Background Art

[0002] Traditional lithium-ion batteries have potential safety issues, and the development of all-solid-state lithium-ion batteries can solve this problem. One of the core elements of all-solid-state lithium-ion batteries is the solid electrolyte, which has better safety performance than liquid electrolytes and has attracted much attention from the industry in recent years. Among the several development routes of solid-state electrolytes, halide / sulfide solid electrolytes have the advantages of high room temperature ionic conductivity and good processing performance, and have good development and application prospects. However, despite this, all-solid-state batteries based on halides / sulfides still have problems such as low electrochemical window and serious interfacial side reactions between the positive and negative electrodes. At the same time, solid electrolyte particles need to be mixed between the positive and negative electrodes, which reduces the energy density to a certain extent, and is still some distance away from commercialization.

[0003] If solid electrolytes are mixed with liquid electrolytes to prepare semi-solid lithium-ion batteries, they have both the high ionic conductivity and high interface wettability of liquid electrolytes and the high safety of solid electrolytes. This is the most promising development route for mass production at this stage. Semi-solid lithium batteries are a compromise between liquid lithium-ion batteries and all-solid lithium-ion batteries. They have certain progress in improving battery safety and energy density, and provide a new industrialization direction for improving power battery performance. Compared with liquid batteries, energy density and safety have been improved.

[0004] However, due to their high reactivity, halide / sulfide solid electrolytes are prone to serious side reactions with organic solvents, causing the electrolyte to deteriorate and cannot be used in combination with traditional carbonate electrolytes. Therefore, it is currently difficult to directly apply them to solid-liquid mixed semi-solid lithium-ion batteries. Summary of the invention

[0005] Based on the above technical problems, the present invention provides a composite solid electrolyte membrane and a semi-solid lithium-ion battery, by coating an oxide solid electrolyte layer with high chemical stability to organic solvents on the surface of a halide / sulfide solid electrolyte film, thereby effectively avoiding the reaction between the sulfide / halide solid electrolyte and the liquid electrolyte, thereby enabling the composite solid electrolyte membrane to be effectively used in solid-liquid mixed semi-solid lithium-ion batteries.

[0006] The present invention provides a composite solid electrolyte membrane, which comprises a halide / sulfide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide / sulfide solid electrolyte film.

[0007] In the present invention, the oxide solid electrolyte layer is coated on the surface of the halide / sulfide solid electrolyte film, which can effectively prevent the liquid electrolyte from penetrating into and contacting the sulfide / halide solid electrolyte, thereby preventing the chemical reaction between the two from causing failure. At the same time, it also avoids direct contact between the sulfide / halide solid electrolyte and the positive and negative electrodes, thereby effectively improving the interface stability.

[0008] Preferably, the halide / sulfide solid electrolyte thin film is formed by pressing the halide / sulfide solid electrolyte into a film by sheeting or rolling;

[0009] Preferably, the halide or sulfide solid electrolyte is Li3InCl6, Li3YCl6, Li3ScCl6, Li3YBr6, Li 1.75 ZrCl 4.75 O 0.5 , Li 0.54 Si 1.74 P 1.44 S 1.7 Cl 0.3 , Li 10 GeP2S 12 or at least one of Li6PS5Cl;

[0010] Preferably, the thickness of the halide / sulfide solid electrolyte film is 10-100 μm.

[0011] Preferably, when the halide / sulfide solid electrolyte is formed into a film by tableting or rolling, the halide / sulfide solid electrolyte is first mixed with a binder;

[0012] Preferably, the mixing method is ball milling, the ball-to-material ratio of ball milling is preferably 5-20:1, the ball milling speed is preferably 300-500 rpm, and the ball milling time is preferably 1-5 h.

[0013] Preferably, the binder is a polyethyleneimine-based polymer;

[0014] Preferably, the polyethyleneimine-based polymer is added in an amount of 0.1-5 wt % of the halide or sulfide solid electrolyte.

[0015] Preferably, the polyethyleneimine-based polymer is obtained by sequentially condensing polyethyleneimine with carboxylated trithiocarbonate and carboxylated polyethylene glycol, and then polymerizing with fluorinated acrylate;

[0016] Preferably, the mass ratio of the polyethyleneimine, carboxylated trithiocarbonate, carboxylated polyethylene glycol and fluorinated acrylate is 100:1-3:10-20:10-30;

[0017] Preferably, the carboxylated trithiocarbonate is at least one of bis(carboxymethyl) trithiocarbonate, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid or 2-(phenylthioformylthio) propionic acid;

[0018] Preferably, the fluorine-containing acrylate is at least one of trifluoroethyl methacrylate, heptafluorobutyl methacrylate, perfluorooctyl ethyl acrylate or perfluorophenyl methacrylate.

[0019] In the present invention, the polyethyleneimine-based polymer has abundant oxygen-containing, fluorine-containing and amino functional groups, which can effectively adsorb and bind the halide / sulfide solid electrolyte, thereby ensuring that the surface of the formed composite electrolyte membrane is dense and smooth, which is helpful for the subsequent deposition to form an oxide solid electrolyte layer, and further enhances the physical isolation effect of the halide / sulfide solid electrolyte relative to the liquid electrolyte. In addition, since the polyethyleneimine-based polymer has excellent flexibility, it can stabilize the solid electrolyte structure and further improve its interface stability, thereby obtaining more excellent cycle stability.

[0020] Preferably, the oxide solid electrolyte layer is formed by depositing the oxide solid electrolyte on the surface of the halide / sulfide solid electrolyte film by magnetron sputtering using the oxide solid electrolyte as a target material.

[0021] In the present invention, a dense oxide solid electrolyte coating is deposited on the surface of the sulfide / halide solid electrolyte film by a magnetron sputtering process, which can effectively prevent the liquid electrolyte from penetrating into and contacting the sulfide / halide solid electrolyte, thereby preventing the chemical reaction between them and causing failure. At the same time, it also avoids direct contact between the sulfide / halide solid electrolyte and the positive and negative electrodes, effectively improving the interface stability.

[0022] Preferably, the oxide solid electrolyte is at least one of lithium phosphorus oxynitride LiPON, lithium lanthanum zirconium oxide LLZO, element-doped lithium lanthanum zirconium oxide LLZXO, lithium lanthanum titanium oxide LLTO, element-doped lithium lanthanum titanium oxide LLTXO, lithium aluminum germanium phosphate LAGP, element-doped lithium aluminum germanium phosphate LAGXP, lithium aluminum titanium phosphate LATP or element-doped lithium aluminum titanium phosphate LATXP;

[0023] Preferably, in the element-doped lithium lanthanum zirconium oxide LLZXO, X is Ta, Nb or Ga, and the content of the doping element is less than 15%, in the element-doped lithium lanthanum titanium oxide LLTXO, X is Zr or Y, and the content of the doping element is less than 15%, in the element-doped lithium aluminum germanium phosphate LAGXP, X is Sm or Zr, and the content of the doping element is less than 15%, in the element-doped lithium aluminum titanium phosphate LATXP, X is Bi or Sn, and the content of the doping element is less than 15%;

[0024] Preferably, the oxide solid electrolyte layer has a thickness of 0.01-1 μm.

[0025] Preferably, the magnetron sputtering parameters include: the sputtering source is a radio frequency sputtering source, and the sputtering power density is 1-5 W / cm 2 , the sputtering pressure is 0.5-1.5 Pa, the sputtering distance is 2-20 cm, the sputtering atmosphere is argon and / or nitrogen, and the sputtering time is 10-180 min.

[0026] The present invention also provides a semi-solid lithium ion battery, comprising a positive electrode, a negative electrode and the composite solid electrolyte membrane.

[0027] In the present invention, the positive electrode active material can be selected as one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, ternary nickel cobalt manganese or ternary nickel cobalt aluminum, and the negative electrode active material can be selected as one of metal lithium sheet, graphite, hard carbon, soft carbon, silicon carbon or lithium titanate.

[0028] Preferably, the semi-solid lithium-ion battery further comprises a liquid electrolyte, wherein the liquid electrolyte comprises a carbonate and a lithium salt;

[0029] Preferably, the carbonate is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate; the lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium dioxalatoborate, lithium difluorooxalatoborate, lithium difluorophosphate or lithium perchlorate.

[0030] Compared with the prior art, the present invention has the following technical effects:

[0031] The present invention provides a composite solid electrolyte membrane and a semi-solid lithium ion battery. By coating an oxide solid electrolyte layer on the surface of a halide / sulfide solid electrolyte film, the reaction between the sulfide / halide solid electrolyte and the liquid electrolyte is avoided, thereby realizing the application of the sulfide / halide solid electrolyte in a solid-liquid mixed semi-solid lithium ion battery, and at the same time significantly improving the interface stability of the positive and negative electrode sides, thereby obtaining excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a cycle performance diagram of the composite solid electrolyte membrane described in Example 1 for a semi-solid lithium-ion battery at a current density of 0.5C;

[0033] Figure 2 This is a schematic diagram of the structure of the polyethyleneimine-based polymer described in Example 1. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0035] Example 1

[0036] This embodiment provides a composite solid electrolyte membrane, comprising a halide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide solid electrolyte film;

[0037] The composite solid electrolyte membrane is prepared by the following method:

[0038] (1) adding a halide solid electrolyte powder (Li3YCl6) and a polyethyleneimine-based polymer in a mass ratio of 99.5:0.5 to a planetary ball mill for uniform mixing, the ball-to-material ratio is 10:1, the ball milling speed is 400 rpm, the ball milling time is 2 h, and the obtained mixed powder is rolled using a roller press at a rolling temperature of 70 ° C to obtain a halide solid electrolyte film with a thickness of 50 μm;

[0039] The polyethyleneimine-based polymer is prepared by the following method:

[0040] Bis(carboxymethyl) trithiocarbonate was added to N,N-dimethylformamide (DMF) and stirred to dissolve completely. N-hydroxysuccinimide (NHS) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) were then added and stirred to dissolve completely. The weight ratio of bis(carboxymethyl) trithiocarbonate, NHS and EDC was 1:1.5:2. Then branched polyethyleneimine (bPEI, M w =1800) DMF solution, the weight ratio of bis(carboxymethyl) trithiocarbonate and branched polyethyleneimine is 1:50, after stirring and reacting for 12 hours, a DMF solution containing carboxylated polyethylene glycol monomethyl ether (mPEG-COOH), NHS and EDC is added dropwise, the weight ratio of branched polyethyleneimine, carboxylated polyethylene glycol monomethyl ether, NHS and EDC is 1:0.15:0.01:0.01, after stirring and reacting for 24 hours, dialyzed in water, and freeze-dried The PEI-PEG-trithiocarbonate was dried to obtain PEI-PEG-trithiocarbonate; the PEI-PEG-trithiocarbonate, hexafluorobutyl methacrylate and azobisisobutyronitrile were added to tetrahydrofuran, the weight ratio of branched polyethyleneimine, hexafluorobutyl methacrylate and azobisisobutyronitrile was 1:0.2:0.002, the temperature was raised to 80°C under nitrogen protection, and the reaction was stirred for 12 hours. After the reaction, n-hexane was added for precipitation, suction filtration, washing, and vacuum drying to obtain the polyethyleneimine-based polymer;

[0041] The carboxylated polyethylene glycol monomethyl ether is prepared by the following method: polyethylene glycol monomethyl ether (mPEG, Mn =1000), succinic anhydride (SA) and 4-dimethylaminopyridine (DMAP) were added to dichloromethane and stirred to dissolve completely, the weight ratio of polyethylene glycol monomethyl ether, SA and DMAP was 1:0.1:0.2, the temperature was raised to 60°C and stirred for reaction for 3h, dichloromethane was removed by rotary evaporation, the mixture was washed with ether and dried to obtain carboxylated polyethylene glycol monomethyl ether;

[0042] (2) The above-mentioned halide solid electrolyte film is used as a substrate, lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2 , the sputtering distance is 5 cm, the sputtering time is 60 min, and an oxide solid electrolyte layer with a thickness of 0.30 μm is formed on both sides of the halide solid electrolyte film, thereby obtaining the composite solid electrolyte membrane.

[0043] Example 2

[0044] This embodiment provides a composite solid electrolyte membrane, comprising a sulfide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the sulfide solid electrolyte film;

[0045] The composite solid electrolyte membrane is prepared by the following method:

[0046] (1) Sulfide solid electrolyte powder (Li 10 GeP2S 12 ) and a polyethyleneimine-based polymer in a mass ratio of 99.5:0.5 were added to a planetary ball mill for uniform mixing, the ball-to-material ratio was 5:1, the ball milling speed was 500 rpm, the ball milling time was 1 h, and the obtained mixed powder was rolled by a roller press at a rolling temperature of 80° C. to obtain a sulfide solid electrolyte film with a thickness of 80 μm; the polyethyleneimine-based polymer was prepared by the method described in Example 1;

[0047] (2) The above-mentioned sulfide solid electrolyte film is used as a substrate, lithium lanthanum titanium oxide (LLTO, Li 0.33 La 0.56 TiO3) was used as the target material, and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is nitrogen, the sputtering pressure is 0.8Pa, and the sputtering power density is 5W / cm 2, the sputtering distance is 3 cm, the sputtering time is 100 min, and an oxide solid electrolyte layer with a thickness of 0.40 μm is formed on both sides of the sulfide solid electrolyte film, thereby obtaining the composite solid electrolyte membrane.

[0048] Example 3

[0049] This embodiment provides a composite solid electrolyte membrane, comprising a halide / sulfide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide / sulfide solid electrolyte film;

[0050] The composite solid electrolyte membrane is prepared by the following method:

[0051] (1) adding halide / sulfide solid electrolyte powder (Li6PS5Cl) and polyethyleneimine-based polymer in a mass ratio of 99.5:0.5 to a planetary ball mill for uniform mixing, the ball-to-material ratio is 20:1, the ball milling speed is 300 rpm, the ball milling time is 5 h, and the obtained mixed powder is rolled by a roller press at a rolling temperature of 75° C. to obtain a halide / sulfide solid electrolyte film with a thickness of 30 μm; the polyethyleneimine-based polymer is prepared by the method described in Example 1;

[0052] (2) The above-mentioned halide / sulfide solid electrolyte film is used as a substrate, lithium germanium aluminum phosphate (LAGP, Li 1.5 A1 0.5 Ge 1.5 (PO4)3) was used as the target material and magnetron sputtering was performed using the radio frequency magnetron sputtering method. The chamber vacuum was 1.0×10 -4 Pa, the working atmosphere is argon / nitrogen mixed gas (volume ratio 2:1), the sputtering pressure is 1.5Pa, and the sputtering power density is 2W / cm 2 , the sputtering distance is 8 cm, the sputtering time is 40 min, and an oxide solid electrolyte layer with a thickness of 0.20 μm is formed on both sides of the halide / sulfide solid electrolyte film, thereby obtaining the composite solid electrolyte membrane.

[0053] Comparative Example 1

[0054] This comparative example proposes a solid electrolyte membrane, which only includes a halide solid electrolyte film;

[0055] The solid electrolyte membrane is prepared by the method described in Example 1, except that step (2) is omitted.

[0056] Comparative Example 2

[0057] This comparative example proposes a solid electrolyte membrane, which only includes a sulfide solid electrolyte film;

[0058] The solid electrolyte membrane is prepared by the method described in Example 2, except that step (2) is omitted.

[0059] Comparative Example 3

[0060] This comparative example proposes a solid electrolyte membrane, which only includes a halide / sulfide solid electrolyte film;

[0061] The solid electrolyte membrane is prepared by the method described in Example 3, except that step (2) is omitted.

[0062] Comparative Example 4

[0063] This comparative example proposes a composite solid electrolyte membrane, comprising a halide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide solid electrolyte film;

[0064] The composite solid electrolyte membrane is prepared by the following method:

[0065] (1) adding halide solid electrolyte powder (Li3YCl6) and polytetrafluoroethylene (PTFE) in a mass ratio of 99.5:0.5 to a planetary ball mill for uniform mixing, the ball-to-material ratio is 10:1, the ball milling speed is 400 rpm, the ball milling time is 2 h, and the obtained mixed powder is rolled by a roller press at a rolling temperature of 70 ° C to obtain a halide solid electrolyte film with a thickness of 50 μm;

[0066] (2) The above-mentioned halide solid electrolyte film is used as a substrate, lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2 , the sputtering distance is 5 cm, the sputtering time is 60 min, and an oxide solid electrolyte layer with a thickness of 0.30 μm is formed on both sides of the halide solid electrolyte film, thereby obtaining the composite solid electrolyte membrane.

[0067] Comparative Example 5

[0068] This comparative example proposes a composite solid electrolyte membrane, comprising a halide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide solid electrolyte film;

[0069] The composite solid electrolyte membrane is prepared by the following method:

[0070] (1) adding a halide solid electrolyte powder (Li3YCl6) and a polyethyleneimine-based polymer in a mass ratio of 99.5:0.5 to a planetary ball mill for uniform mixing, the ball-to-material ratio is 10:1, the ball milling speed is 400 rpm, the ball milling time is 2 h, and the obtained mixed powder is rolled using a roller press at a rolling temperature of 70 ° C to obtain a halide solid electrolyte film with a thickness of 50 μm;

[0071] The polyethyleneimine-based polymer is prepared by the following method:

[0072] Branched polyethyleneimine (bPEI, M w =1800) was added into DMF and stirred to dissolve completely, and then a DMF solution containing carboxylated polyethylene glycol monomethyl ether (mPEG-COOH), NHS and EDC was added dropwise, and the weight ratio of branched polyethylene imine, carboxylated polyethylene glycol methyl ether, NHS and EDC was 1:0.15:0.01:0.01, and the reaction was stirred for 24 hours, and then dialyzed in water and freeze-dried to obtain the polyethylene imine-based polymer;

[0073] The above carboxylated polyethylene glycol monomethyl ether is prepared by the method described in Example 1;

[0074] (2) The above-mentioned halide solid electrolyte film is used as a substrate, lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2 , the sputtering distance is 5 cm, the sputtering time is 60 min, and an oxide solid electrolyte layer with a thickness of 0.30 μm is formed on both sides of the halide solid electrolyte film, thereby obtaining the composite solid electrolyte membrane.

[0075] The solid electrolyte membrane obtained in the above-mentioned embodiment 1 and comparative examples 1, 4, and 5 is directly placed between the lithium metal negative electrode and the NCM622 positive electrode, and a 1M lithium hexafluorophosphate LiPF6 / ethylene carbonate EC+diethyl carbonate DEC (1:1, mass ratio) liquid electrolyte is used to wet the positive and negative electrode interfaces and infiltrate the interior of the porous electrode. After packaging, a Li||NCM622 solid-liquid mixed semi-solid lithium ion battery is obtained.

[0076] The solid electrolyte membrane obtained in the above-mentioned Example 2 and Comparative Example 2 is directly placed between the graphite negative electrode and the LiFePO4 positive electrode, and a 1M lithium hexafluorophosphate LiPF6 / ethylene carbonate EC+diethyl carbonate DEC (1:1, mass ratio) liquid electrolyte is used to wet the positive and negative electrode interfaces and infiltrate the interior of the porous electrode. After packaging, a graphite||LiFePO4 solid-liquid mixed semi-solid lithium ion battery is obtained.

[0077] The solid electrolyte membrane obtained in the above-mentioned Example 3 and Comparative Example 3 is directly placed between the silicon-carbon negative electrode and the LiCoO2 positive electrode, and a 1M lithium hexafluorophosphate LiPF6 / ethylene carbonate EC+diethyl carbonate DEC (1:1, mass ratio) liquid electrolyte is used to wet the positive and negative electrode interfaces and infiltrate the interior of the porous electrode. After packaging, a silicon-carbon||LiCoO2 solid-liquid mixed semi-solid lithium-ion battery is obtained.

[0078] The full battery cycle performance was tested on the Xinwei battery test system (25°C). For Li||NCM622 batteries, the charge and discharge voltage range was 2.8-4.2V, and the charge and discharge current was 0.5C; for graphite||LiFePO4 batteries, the charge and discharge voltage range was 2.2-3.65V, and the charge and discharge current was 0.5C; for silicon-carbon||LiCoO2 batteries, the charge and discharge voltage range was 3-4.2V, and the charge and discharge current was 0.5C. The test results are shown in Tables 1 and Figure 1 .

[0079] Table 1 Comparison of the performance of the semi-solid lithium ion batteries obtained in the examples and comparative examples

[0080]

[0081]

[0082] It can be seen from the results in Table 1 above that Examples 1-3 of the present invention can effectively improve the cycle stability of the semi-solid lithium ion battery. Comparative Examples 1-3 without an oxide solid electrolyte layer cannot solve the problem of instability of the semi-solid lithium ion battery to the liquid electrolyte, and cannot be normally charged, discharged and cycled. Comparative Examples 4 and 5, in which the binder is polytetrafluoroethylene or other types of polyethyleneimine-based polymers, have poor cycle performance relative to Example 1.

[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A composite solid electrolyte membrane, characterized in that: It comprises a halide / sulfide solid electrolyte film and an oxide solid electrolyte layer coated on the surface of the halide / sulfide solid electrolyte film.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The halide / sulfide solid electrolyte film is formed by pressing the halide / sulfide solid electrolyte into a film by sheeting or rolling; Preferably, the halide / sulfide solid electrolyte is Li3InCl6, Li3YCl6, Li3ScCl6, Li3YBr6, Li 1.75 ZrCl 4.75 O 0.5 , Li 0.54 Si 1.74 P 1.44 S 1.7 Cl 0.3 , Li 10 GeP2S 12 or at least one of Li6PS5Cl; Preferably, the thickness of the halide / sulfide solid electrolyte film is 10-100 μm.

3. The composite solid electrolyte membrane according to claim 2, characterized in that: When the halide / sulfide solid electrolyte is formed into a film by tableting or rolling, the halide / sulfide solid electrolyte is first mixed with a binder; Preferably, the mixing method is ball milling, the ball-to-material ratio of ball milling is preferably 5-20:1, the ball milling speed is preferably 300-500 rpm, and the ball milling time is preferably 1-5 h.

4. The composite solid electrolyte membrane according to claim 3, characterized in that: The binder is a polyethyleneimine-based polymer; Preferably, the polyethyleneimine-based polymer is added in an amount of 0.1-5 wt % of the halide / sulfide solid electrolyte.

5. The composite solid electrolyte membrane according to claim 4, characterized in that: The polyethyleneimine-based polymer is obtained by sequentially condensing polyethyleneimine with carboxylated trithiocarbonate and carboxylated polyethylene glycol, and then polymerizing with fluorinated acrylate; Preferably, the mass ratio of the polyethyleneimine, carboxylated trithiocarbonate, carboxylated polyethylene glycol and fluorinated acrylate is 100:1-3:10-20:10-30; Preferably, the carboxylated trithiocarbonate is at least one of bis(carboxymethyl) trithiocarbonate, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid or 2-(phenylthioformylthio) propionic acid; Preferably, the fluorine-containing acrylate is at least one of trifluoroethyl methacrylate, heptafluorobutyl methacrylate, perfluorooctyl ethyl acrylate or perfluorophenyl methacrylate.

6. The composite solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The oxide solid electrolyte layer is formed by using the oxide solid electrolyte as a target material and depositing it on the surface of the halide / sulfide solid electrolyte film by magnetron sputtering.

7. The composite solid electrolyte membrane according to claim 6, characterized in that: The oxide solid electrolyte is at least one of lithium phosphorus oxynitride LiPON, lithium lanthanum zirconium oxide LLZO, element-doped lithium lanthanum zirconium oxide LLZXO, lithium lanthanum titanium oxide LLTO, element-doped lithium lanthanum titanium oxide LLTXO, lithium aluminum germanium phosphate LAGP, element-doped lithium aluminum germanium phosphate LAGXP, lithium aluminum titanium phosphate LATP or element-doped lithium aluminum titanium phosphate LATXP; Preferably, in the element-doped lithium lanthanum zirconium oxide LLZXO, X is Ta, Nb or Ga, and the content of the doping element is less than 15%, in the element-doped lithium lanthanum titanium oxide LLTXO, X is Zr or Y, and the content of the doping element is less than 15%, in the element-doped lithium aluminum germanium phosphate LAGXP, X is Sm or Zr, and the content of the doping element is less than 15%, in the element-doped lithium aluminum titanium phosphate LATXP, X is Bi or Sn, and the content of the doping element is less than 15%; Preferably, the oxide solid electrolyte layer has a thickness of 0.01-1 μm.

8. The composite solid electrolyte membrane according to claim 6 or 7, characterized in that: The magnetron sputtering parameters include: the sputtering source is a radio frequency sputtering source, and the sputtering power density is 1-5W / cm 2 , the sputtering pressure is 0.5-1.5 Pa, the sputtering distance is 2-20 cm, the sputtering atmosphere is argon and / or nitrogen, and the sputtering time is 10-180 min.

9. A semi-solid lithium-ion battery, characterized in that: It comprises a positive electrode, a negative electrode and the composite solid electrolyte membrane according to any one of claims 1 to 8.

10. The semi-solid lithium-ion battery according to claim 9, characterized in that: Also included is a liquid electrolyte, the liquid electrolyte comprising a carbonate and a lithium salt; Preferably, the carbonate is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate; the lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium dioxalatoborate, lithium difluorooxalatoborate, lithium difluorophosphate or lithium perchlorate.